Interdental Papilla Regeneration: The Updates on Several Techniques - Abdul Hayei, Nur Ayman; M. Yusof, Hazira (European Journal of General Dentistry, 2023)
The procedure for regenerating interdental papilla is complex and technique-sensitive. However, the patient demand to reduce black triangle has dramatically increased in recent years. This article aimed to review the most recent surgical techniques on interdental papilla regeneration by reporting studies published from 2016 to 2021. A literature search was performed in electronic databases, including PubMed, Medline, and Web of Science using the following keywords: “interdental papilla regeneration,” “papillary reconstruction,” “surgical papillary regeneration,” and “hyaluronic acid injection.” Studies that have involved surgical techniques for interdental papilla regeneration as well as less invasive surgical procedure such as hyaluronic acid injections are comprehensively reviewed in this article. Techniques such as tunnelling and coronally advanced flap appear to have better success rate compared to other techniques. In view of graft, connective tissue graft resulted in successful interdental papilla regeneration with papillary fill maintained over long-term compared to concentrated growth factors. A less invasive option would be hyaluronic acid injection, but with less success rate compared to surgical procedures. However, the results were limited by the lack of standardised method to measure successful interdental papilla regeneration. This article comprehensively reviews the updates on interdental papilla regeneration techniques.
Keywords: interdental papilla regeneration; black triangle; papillary reconstruction; surgical papillary regeneration; hyaluronic acid injection